Robotic Surgery for Ulcerative Colitis - Anderson, Marissa; Grucela, Alexis (Clinics in Colon and Rectal Surgery, 2021)
Subtotal colectomy (STC) or total proctocolectomy (TPC) and ileal pouch–anal anastomosis (IPAA) performed in two or three stages remain the procedure of choice for patients with ulcerative colitis (UC). Minimally invasive laparoscopic approaches for STC and IPAA have been established for over a decade, having been shown to reduce postoperative pain, length of stay, and improve fertility. However “straight-stick” laparoscopy has ergonomic and visual disadvantages in the pelvis, which may contribute to IPAA failure. The robotic platform was developed to overcome these limitations. Robotic STC is associated with lower conversion rates and earlier return of bowel function with acceptably longer operative time (mean, 28 minutes) than laparoscopic STC. The robotic approach has also been shown in case series to be safe in urgent settings. Robotic IPAA is associated with lower blood loss and length of stay than laparoscopic IPAA. Robotic TPC/IPAA has been shown in small case series to be safe and feasible despite longer operating times.
Keywords: ulcerative colitis; robotic surgery; ileal pouch–anal anastomosis; colectomy